Sharia-Based Innovation Performance: The Role of Dynamic Technological Agility and Entrepreneurial Orientation (IQTISHADIA, 2024)
This study aims to analyze the relationship between dynamic technological agility based on entrepreneur orientation and network resources towards sharia-based innovation performance and competitive advantage in small medium enterprises of Muslim fashion. Specifically, this study argues that dynamic technological agility moderates the relationship between entrepreneur orientation and network resources with sharia-based innovation performance and competitive advantage. Managers and owners of small medium enterprises at Muslim fashion were chosen as the primary focus of this study. 200 questionnaires were distributed managers and owners of small medium enterprises at Muslim fashion. Following the analysis of data from 163 managers and owners of small medium enterprises at Muslim fashion, empirical testing shows that the entrepreneur orientation and the network resources influences the dynamic technological agility and has a strong correlation. This research finds that  dynamic technological agility has a significant impact on sharia-based innovation performance. Meanwhile, the dynamic technological agility and the sharia-based innovation performance influences the competitive advantage.